Membangun Pengalaman Belajar Positif Melalui Integrasi Mind Mapping dan Quizizz Pada Pembelajaran Ekonomi - Fitriyanti Fitriyanti (FKIP, Universitas Palangka Raya, 2026)
Creating meaningful learning experiences has become one of the main challenges in economics education, particularly in promoting active participation and sustained student interest throughout the learning process. Conventional instructional approaches often emphasize content delivery rather than facilitating engaging learning experiences that encourage students to explore, interact, and reflect on economic concepts. This study aims to describe students' learning experiences following the integration of Mind Mapping and Quizizz in economics learning. The research employed a pre-experimental design using a one-group pretest-posttest approach involving 64 eleventh-grade students at SMA Srijaya Negara Palembang during the School Lecturer Program (Program Dosen ke Sekolah). Learning activities were conducted through five meetings integrating Mind Mapping to organize concepts and Quizizz as a digital formative assessment tool. Data were collected using observation sheets, learning motivation questionnaires, learning outcome tests, and classroom documentation. The findings indicate that integrating Mind Mapping and Quizizz created a more positive learning experience. Students demonstrated higher participation, stronger enthusiasm during classroom activities, greater confidence in expressing ideas, and more active interaction with peers and teachers. Learning motivation increased from 62% to 85%, while classroom activity improved from 60% to 82%. Although the improvement in learning outcomes remained relatively low (N-Gain = 0.22), students perceived the learning process as more enjoyable, interactive, and easier to understand than conventional instruction. These findings suggest that learning experience should be considered an important indicator in evaluating instructional innovation because positive learning experiences may become the foundation for improving students' long-term learning